2019
DOI: 10.1016/j.jhepr.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

New treatments/targets for primary biliary cholangitis

Abstract: Primary biliary cholangitis (PBC) is an autoimmune, cholestatic, chronic liver disease that ultimately progresses towards cirrhosis and liver failure if untreated. While ursodeoxycholic acid has been established as standard of care for PBC in the last few decades, significant advances in second-line treatment options have recently been made and new therapeutic developments are currently under evaluation. The purpose of this article is to provide the clinician with an overview of the current treatment options a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 82 publications
0
19
0
2
Order By: Relevance
“…Thus, a substantial number of patients with each of the three diseases progress to cirrhosis and liver failure and, although each is rare, collectively, they represent an important indication for liver transplantation. A better comprehension of the pathways driving each individual disease might facilitate the successful development of highly warranted effective therapies (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a substantial number of patients with each of the three diseases progress to cirrhosis and liver failure and, although each is rare, collectively, they represent an important indication for liver transplantation. A better comprehension of the pathways driving each individual disease might facilitate the successful development of highly warranted effective therapies (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…OCA and fibrates should be considered in any patient with incomplete response to UDCA, considered by most guidelines as ALP >1.5× ULN or elevated levels of total bilirubin. Importantly, it is anticipated that more stringent biochemical response criteria may be used in the future, because emerging evidence suggests that complete normalization of ALP provides additive value in predicting outcomes in PBC 11 . As a consequence, we expect increasing use of combination therapies as an important next frontier in the treatment of PBC.…”
Section: Discussionmentioning
confidence: 99%
“…UDCA promotes biliary HCO 3 − secretion and therefore strengthens the defensive alkaline barrier, which protects BECs [ 61 ▪▪ ]. The fact that most PBC patients have a positive response to UDCA while immunosuppressive drugs (including newer biologics used to modify the immune system) do not provide a clear benefit [ 19 , 64 68 ] supports the notion that AE2 deficiency and a defective biliary HCO 3 − umbrella are key determinants of bile duct damage in PBC. The mechanisms by which UDCA increases biliary HCO 3 − secretion involve the activation of PI3K/Akt pathway, which stimulates the release of ATP leading to the extrusion of Cl − to the lumen through the Ca 2+ -dependent Cl − channel TMEM16A and subsequent Cl − /HCO 3 − exchange [ 61 ▪▪ ].…”
Section: Biliary Epithelial Cell Dysfunction In Primary Biliary Cholamentioning
confidence: 99%
“…Indeed, PBC patients who respond favorably to UDCA (more than 60%) have a life expectancy similar to that of age and sex-matched normal population [ 16 18 ]. With ongoing development of novel therapies, combination regimes are expected to achieve adequate control of the disease in those patients who do not respond to UDCA alone [ 11 , 19 , 20 ]. In fact, sufficiently powered phase III clinical trials have shown that two drugs, the FXR agonist obeticholic acid and bezafibrate (a PPAR-α agonist that reduces bile salt synthesis and increases biliary phospholipid secretion), provide benefit in combination with UDCA to patients with incomplete response to UDCA monotherapy [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%